A educação popular nas experiências e práticas de integração curricular no PROEJA do IFES - Scopel, Edna Graça (2017)
The problem issue that instigated this research reports to the way in which the experiences lived in the Proeja’s educational practices explicit the search for the curricular integration and the collective construction, in the perspective of the popular education. It has as general objective to analyze the experiences of the subjects involved in Proeja, in the Ifes - Campus Vitória, in contexts of differentiated educational practicesin aiming at the curricular integration and collective construction.The epistemological fundamentals of popular education, from a liberating perspective, are taken as the main theoretical and methodological contribution, to dialogue with practices and experiences In Proeja’s scope, from the field of studies produced in the Latin American context, characterized by a proper thought and a political and pedagogical practice of resistance to domination and neoliberal hegemonic thinking, having as basic option the transformation of the conditions that perpetuate inequality, injustice and social exclusion.We worked with the hypothesis that the Proeja, over 10 years of its implementation, has produced Innumerable experiences that, despite their contradictions, have been expressed in the observed changes in educational practices that incorporate some principles of popular education, in the search for curricular integration.We worked with the systematization of experiences as a methodological strategy, supported by the deconstructive epistemological approach and historical-dialectic, Attempting to the critical and analytical posture and the estrangement of who carry it out, and to the conditions of the context and the historical moment of realization of the experiences , Which involved 25 educators, 15 students and 5 gestores. The analyzes were performed from the production from records of the pedagogical meetings, the field diary, interviews and observations in loco. The experiences here systematized lead us to reaffirm the thesis that the epistemological foundations and practices of popular education constitute an alternative to rethink the educational processes in Proeja on Campus Vitória.The results indicate the protagonism of the subjects, their critical reflections about the practices in order to understand them and produce interferences in what demand transformation. In spite of the contradictions, is perceived the exercise of dialogue with one of the principles of the integrated curriculum, in the collective construction of general and specific knowledge.